Numerical analysis of tissue heating using the bioheat transfer porous model - Majchrzak, Ewa; Turchan, Łukasz (Computer Assisted Methods in Engineering and Science, 2013)
The paper concerns the modelling of artificial hyperthermia. The 3D domain including healthy tissue and tumor region is considered. Heat transfer processes proceeding in this domain are described by the Pennes model and next by the porous one. The external heating of tissue is taken into account by the introduction of internal source function to the equation considered. Both models are supplemented by the same geometrical, physical, boundary and initial conditions. At the stage of numerical simulation the explicit scheme of finite difference method is used. The examples of computations show the similarities and differences of solutions and allow to formulate the conclusions connected with the applications of the results obtained in the hyperthermia therapy.